(untitled) - Morse, Edward S. (New York, 1961)
This book consists of the following many parts: the house, types of houses, interiors, entrances and approches, gatdens, miscellaneous matters, the ancient house, the neighboring house.
Keywords: Architecture, domestic,Interior decoration; Japan,Japan